Pharmacokinetics of Gepotidacin in Subjects With Normal Hepatic Function and Hepatic Impairment. Issue 6 (15th January 2021) - Hossain, Mohammad; Tiffany, Courtney; Tao, Yu; Barth, Aline; Marbury, Thomas C.; Preston, Richard A.; Dumont, Etienne
Abstract: Gepotidacin is a novel triazaacenaphthylene bacterial topoisomerase inhibitor. This phase 1 nonrandomized, open‐label, multicenter, 2‐part study evaluated the pharmacokinetics, safety, and tolerability of oral gepotidacin 1500 mg in 3 different hepatic settings (normal, moderate impairment, and severe impairment). Gepotidacin was safe and generally tolerated in all subjects. Compared to subjects with normal hepatic function, gepotidacin plasma area under the plasma concentration–time curve from time 0 to infinity (AUC0–∞ ) and maximum concentration significantly increased by 1.7‐ and 1.9‐fold, respectively, in severe hepatic impairment; increases in moderate impairment were not statistically significant. No significant effect was observed for gepotidacin plasma elimination half‐life (geometric mean range, 8.2–9.1 hours) across hepatic groups. Renal clearance increased in moderate (16%) and severe (52%) hepatic impairment vs normal. The mean fraction of gepotidacin dose excreted in urine increased with increasing hepatic impairment (normal, 7.5%; moderate, 11.2%; and severe, 19.9%). Urine gepotidacin concentrations remained high for 12 hours in all hepatic groups after dosing. Saliva gepotidacin concentrations displayed a linear relationship with plasma concentrations (R 2 = 0.76). The ratio of saliva AUC to unbound plasma AUC and elimination half‐life were not affected by hepatic impairment. These data indicate that gepotidacin dose adjustment is not required in mild to moderate hepatic impairment; severe hepatic impairment may require increases in dosing interval or dose reduction.